USE OF MANAGEMENT INFORMATION SYSTEMS TO IMPROVE EFFICIENCY AND EFFECTIVENESS OF MEDAN CITY GOVERNMENT - Juwita Sihotang; Tiurlan Manullang; Munthe, Tino Osama; Irwan Nopian Sinaga (CV Naskah Aceh, 2025)
This research aims to examine the implementation of the Management Information System (MIS) within the Medan City Regional People's Representative Council (DPRD) and its impact on operational efficiency and public service effectiveness. Using a descriptive qualitative approach, data were collected through interviews with interns placed in the Bapemperda section. The findings indicate that the information system has assisted in the execution of administrative tasks; however, the effectiveness of its implementation is still influenced by human resource factors, particularly in terms of task placement that aligns with individual competencies. A lack of understanding in certain work areas leads to ineffectiveness in task execution. This study recommends the need for improved communication between educational institutions, interns, and government agencies to ensure appropriate placement of interns. Additionally, enhancing capacity and training related to the use of information systems is also crucial to support efficiency and effectiveness in government performance.